Diagnóstico de la demanda de energía en el sistema de transportación de hormigonera napo de la ciudad de Latacunga, provincia de Cotopaxi, en el año 2015. Propuesta de acciones, medidas y aspectos claves para la disminución del consumo de combustible en la producción de hormigón - Acurio León, Carlos Manuel (2016)
In this work the situation of industrial production of concrete, development of a strategy to recapitalize and automation of facilities and energy impact and the importance of monitoring and recording of energy indices are analyzed for electricity and carriers energy consumed, the decentralization policy of concrete to reduce energy consumption in the transport phase distance of fresh concrete mix and the need for training of the technical workforce. The concrete plant company operates transportation systems of raw materials through the same conveyor belts that run an electric generator that works with an internal combustion engine Russian-made works Deutz diesel powered fuel; bands and rollers are elements that help to receive a product of almost continuous and regular to drive to another point, the work of the bands in the concrete mixer is the transfer of concrete aggregates to the mixing zone, but when making this activity can appreciate a fuel consumption based on the interview question two on the Manager of the Napo Company, which was able to say that he has explored concrete mixers similar characteristics especially in the city of Machachi Pichincha Province and it establishes that at least consumes 10% less than the concrete mixer that management, this was the reason that inspired this study. Finally the proposed alternative solutions to the problem of energy efficiency in the production of concrete, in parallel with the definition of minimum ecological requirements of these facilities to ensure sustainability for this type of installation and thus reduce production costs by improving plant productivity Napo concrete city of Latacunga Cotopaxi province.